2012
DOI: 10.5897/jphe12.058
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer knowledge and screening practices among women in selected rural communities of Nigeria

Abstract: Globally, the devastation that befalls women diagnosed of breast cancer remains inestimable. Early detection remains a major effective approach that should be employed to combat the disease. The issue of concern, however, is whether women in the rural underserved areas are aware of these early detection methods. This study was designed to assess rural women's awareness and knowledge of breast cancer and their screening practices. The study was a descriptive cross-sectional study utilizing self developed struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…32 In a related study, 27.3% of women in Oyo state practiced BSE but only 11.7% practiced it regularly. 34 Moreover, the reasons for the low rate of practice of BSE among women include; fear of finding that they have breast cancer, fear of finding a lump, inadequate knowledge regarding how to perform BSE, forgetfulness, dislike to touch breast, absence of breast complaints and lack of awareness about what to do if a lump is found. 37 These barriers can be eliminated through BSE education to women.…”
Section: Introductionmentioning
confidence: 99%
“…32 In a related study, 27.3% of women in Oyo state practiced BSE but only 11.7% practiced it regularly. 34 Moreover, the reasons for the low rate of practice of BSE among women include; fear of finding that they have breast cancer, fear of finding a lump, inadequate knowledge regarding how to perform BSE, forgetfulness, dislike to touch breast, absence of breast complaints and lack of awareness about what to do if a lump is found. 37 These barriers can be eliminated through BSE education to women.…”
Section: Introductionmentioning
confidence: 99%
“…A slightly different result was found by Olowokere, Onibokun and Oluwatosin, [27] who assess rural women's awareness and knowledge of breast cancer and their screening practices in selected rural communities of Nigeria and a significant association was revealed between the educational status of women and their practices for clinical breast examination which means that the higher the educational status of women, the more the likelihood that they are going to participate in screening test for breast cancer. Also a study done by Ozmen et al, (2009) [28] among the Turkish women to clarify the risk for breast cancer, concluded that higher education does not mean that people will follow all the health guidelines because some highly educated people still lack the awareness to make correct health decisions.…”
Section: Discussionmentioning
confidence: 88%
“…A lower result was found by Onwere et al, (2009) [45] when determine antenatal women's knowledge and practice of breast self-examination as a method of early detection of breast cancer only 1% and 2% of their respondents had clinical breast examination performed by doctors and nurses. Also the study done by Olowokere et al [27] found that, clinical breast examination was known among 51.7% of the women and 31.7% of them confirmed that they had breast examination by health professionals, however, 38.9% of the women could not correctly ascertain the ideal frequency for performing the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women that practiced BSE are older than those who did not practice BSE. While, other studies indicate no significant relationship exist between the age of the respondents and the knowledge and practice of BSE 24,25,26,27 . There are no studies conducted in Sokoto to explore the relationship between the age and Breast SelfExamination among women.…”
Section: Introductionmentioning
confidence: 86%